Escherichia coli spontaneous community-acquired meningitis in adults: A case report and literature review. (February 2018) - Bichon, A.; Aubry, C.; Dubourg, G.; Drouet, H.; Lagier, J.-C.; Raoult, D.; Parola, P.
Highlights: Spontaneous community-acquired Escherichia coli meningitis is poorly reported in the literature, with only 43 cases described since 1946. The annual incidence of spontaneous community-acquired E. coli meningitis is underestimated, ranging from 2 to 5 cases per 100 000 persons. Nine percent of diagnosed patients were previously healthy. The mortality rate was found to be higher than for other bacterial meningitides, at up to 100%. Systematic screening for strongyloidiasis should be performed for symptomatic patients returning from an endemic area. Abstract: Gram-negative bacillary meningitis occurring post-trauma and following neurosurgical procedures has been described widely. However, reports of spontaneous cases are sparse, particularly community-acquired cases. Spontaneous community-acquired Escherichia coli meningitis is a rare (although increasingly seen) and specific entity that is poorly reported in the literature. A review of the literature identified only 43 cases of community-acquired E. coli meningitis reported between 1946 and 2016. This article describes two new cases of spontaneous community-acquired E. coli meningitis encountered in Marseille, France, and presents the results of a literature review on spontaneous community-acquired E. coli meningitis.